1999
DOI: 10.1109/3.753666
|View full text |Cite
|
Sign up to set email alerts
|

Transient response of vertical-cavity surface-emitting lasers of different active-region diameters

Abstract: Abstract-The multimode dynamics of vertical-cavity surfaceemitting lasers with different active-region diameters was measured under subnanosecond electrical excitation (800-ps pulse duration, 100-ps risetime). The dynamics is characterized by the delayed onset of higher order modes which have a turn-on delay that is dependent on the active-region diameter and the excitation parameters. A simple model that can be used to estimate this turn-on delay for large-area devices is presented. Polarizationresolved measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
9
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
5
9
1
Order By: Relevance
“…Modeling results concerning the turn-on behavior also indicate that the laser starts to emit in low order modes due to their lower threshold, compared with higher order modes [15]. Spectrally, however, not spatially resolved experiments performed by Buccafusca et al [7], [8], [19] agree very well with the observed behavior. The set of excited modes during the first relaxation oscillation peak depends on pumping conditions, and there is little change in the relative intensity increase among the modes, indicating that during this time the threshold behavior of each mode dominates the evolution of the near-field intensity [8].…”
Section: Analysis Of the Underlying Mechanismssupporting
confidence: 75%
See 2 more Smart Citations
“…Modeling results concerning the turn-on behavior also indicate that the laser starts to emit in low order modes due to their lower threshold, compared with higher order modes [15]. Spectrally, however, not spatially resolved experiments performed by Buccafusca et al [7], [8], [19] agree very well with the observed behavior. The set of excited modes during the first relaxation oscillation peak depends on pumping conditions, and there is little change in the relative intensity increase among the modes, indicating that during this time the threshold behavior of each mode dominates the evolution of the near-field intensity [8].…”
Section: Analysis Of the Underlying Mechanismssupporting
confidence: 75%
“…Spectrally, however, not spatially resolved experiments performed by Buccafusca et al [7], [8], [19] agree very well with the observed behavior. The set of excited modes during the first relaxation oscillation peak depends on pumping conditions, and there is little change in the relative intensity increase among the modes, indicating that during this time the threshold behavior of each mode dominates the evolution of the near-field intensity [8]. The appearance of higher order modes and their dynamical behavior has been experimentally shown by Giudici et al with the help of a streak camera [9].…”
Section: Analysis Of the Underlying Mechanismssupporting
confidence: 74%
See 1 more Smart Citation
“…Spectrally, however not fully spatially resolved experiments performed by Buccafusca et al 7,8,14 agree very well with the observed behavior. The set of excited modes during the first 100 ps after turn-on depends on pumping conditions, and there is little change in the relative intensity increase among the modes, indicating that during this time the threshold behavior of each mode dominates the evolution of the spectral emission properties.…”
supporting
confidence: 77%
“…Physical insight into the underlying mechanisms and laser-matter interaction determining the dynamics is desired. Until recently, mainly spatially integrated 7,8 and one-dimensional cuts 9 of the time-resolved dynamics of the near-field intensity had been published, precluding investigations of the dynamics of the full 2-D-spatial interactions.…”
Section: Introductionmentioning
confidence: 99%